Contribuição de iniciativas de cidades inteligentes no desenvolvimento humano : uma análise da percepção de agentes de centros de operações municipais no Brasil - Pereira, Gabriela Viale (2016)
Cities around the world are facing complex challenges from the growing urbanization. The lack of policies for the welfare and safety of individuals results in the increase of urban problems, especially considering the rapid urbanization phenomenon. The people's well-being is influenced by the freedoms they live and their ability to respond and recover from adverse events, including natural or technological. However, natural disasters and human-induced crises still lead to loss of life, undermining the livelihoods and development. Cities have an important role for human and social development being governments strategically responding to it by encouraging the proliferation of smart cities initiatives. The combination of a set of business processes and technology resources the government goes forward in improving the delivery of information and public services to society. From providing information and services relevant to citizens and in real time increase the chances of the government provides the appropriate services for specific populations. In this regard, centers of municipal operations have an important role in responding to social events and natural disasters, as a way to address the urgency and dynamism of urban problems. Thus, this research aims to analyze how the centers of municipal operations contribute to human development. This research also seeks to analyze how the centers of municipal operations are understood and implemented and how the delivery of information and public services can be converted into functionings and capabilities as a result of human development. The main theoretical lens adopted to study the human development phenomenon is the capability approach, which provides the basis for evaluating the individual and social well-being and served as the basis for creating the conceptual model that guides this research. The proposed conceptual model suggests that the achievement of better results in smart cities initiatives is related to its contribution to human development, which primarily deals with increasing opportunities, i.e. capabilities, so that people have the life they want. In order to explore how this phenomenon occurs it was conducted an exploratory study, based on multiple case studies. The empirical setting of this research is determined by the centers of municipal operations in Rio de Janeiro, Porto Alegre and Belo Horizonte. The research findings evidenced that the implementation of centers of municipal operations involve technological, organizational and managerial factors, in addition to political and institutional factors. The main results of the initiatives were analyzed, considering aspects related to smart cities governance, such as communication, participation, partnership and collaboration, transparency and accountability, as well as efficiency and effectiveness in public administration. By tracing the main activities of the centers of municipal operations and outputs of this process, it was found that the improvement in the provision and delivery of information and public services results in resources that contribute extending the capabilities as a prerequisite for human development. Finally, it was found that the increased capabilities enables the achievement of functionings both in terms of fundamental aspects of human development, and in creating conditions for human development, being the functiong conditioned by individual's choice.